Synthetic Polymeric Membranes - Khulbe, K. C. (Springer, 2017)
Tis book concentrates on atomic force microscopy (AFM), a method recently - veloped to study the surfaces of synthetic polymeric membranes. AFM is becoming a very important tool for the characterization of synthetic polymeric membranes. Te development of membranes of improved performance depends on the exact kn- ledge of the morphology of a thin selective layer that exists at the surface of the m- brane. Te control of the morphology of the selective layer is crucial for the design of synthetic polymeric membranes. With a relatively short history of only twen- ?ve years, AFM has ?rmly established its position as a method to characterize the membrane surface. Each chapter of this book includes information on basic principles, commercial applications, current research, and guidelines for future research. Each chapter is summarized at the end and contains a comprehensive list of references. Te introductory chapter gives a brief overview of synthetic polymeric m- branes and their applications both in industrial processes and in biomedical ?elds. It also gives an overview of studies on membrane surface morphology by various methods. Chapter ? deals with the synthesis of membranes, the properties of membranes, and the application of membranes. Te beginning also identi?es the three types of membranes (i.e., biological, synthetic, and theoretical) and their applications.